(untitled) (New Jersey, 2002)
Proceedings of the Second Meeting on CPT and Lorentz Symmetry, held August 15-18, 2001 in Bloomington, IN, USA. For theoretical and experimental physicists with an interest in relativity and space-time symmetries.
Keywords: CP violation (Nuclear physics),Lorentz groups